Managing asymmetric conflict - Paul Dunne; María del Carmen García-Alonso; Paul Levine; Ron Smith (University of Kent, Department of Economics, 2004)
We consider conflicts between an incumbent, e.g. government or dominant firm, and potential challengers, e.g. guerilla movement or entrants. It is not uncommon for challengers to win such conflicts despite their lack of resources. They can do this by exploiting a second mover advantage: choosing to attack the incumbent in ways that it had not prepared for, because it was locked in by past investments. To model such asymmetric conflict we use a three stage game. In the first stage the incumbent chooses effort; in the second stage the challengers choose the degree of differentiation from the incumbent and in the third stage each decide whether to attack or defend and collect their payoffs. This simple model has a number of interesting predicitions, which may apply in certain types of legal, commercial and military conflicts.
Keywords: L10; D74; 330; Game theory; product differentiation; conflict; Wettbewerbsstrategie; Produktdifferenzierung; Spieltheorie